Penerapan Rantai Markov Dalam Peramalan Cuaca (Studi Kasus: Cuaca Harian di Kota Padang) - Winda Fransiska; Ririn Hayatun Nufus; Lilis Harianti Hasibuan; Mohamad Syafi’i (Universitas PGRI Adi Buana Surabaya, 2022)
Information about the weather is needed. Weather is one of the considerations of the community in carrying out various activities. The purpose of this study is to provide information related to weather forecasts by applying Markov chain theory. The Markov chain is a random process in which all information about the future is contained in the present state. The study uses daily weather data that occurs on June 1, 2022 to June 30, 2022 to predict the weather for the next 7 days. The data used is secondary data taken from the website of the Meteorology, Climatology, and Geophysics Agency (BMKG) of Padang City. Based on the results of calculations using Markov chains, a transition matrix is obtained that is used to predict the weather for the next day.